When the winners are the losers: Invasive alien bird species outcompete the native winners in the biotic homogenization process. (January 2020) - Colléony, Agathe; Shwartz, Assaf
Highlights: There are several potential winners in the process of biotic homogenization (BH). We show that non-native bird species outcompete native ones in the BH. In Israel, common native birds have been declining in the last 15 years. In contrast, there were 250 %–800 % increases in non-native populations. In particular, common mynas appear to drive declines of house sparrows. Abstract: Species are declining worldwide, but while some are becoming threatened, few others thrive under novel environmental conditions. Land use changes and biological invasion are the main drivers of this 'biotic homogenization' (BH) that increasingly occurs in human-dominated landscapes. Among birds, several groups of species have been identified as 'winners' in this process (e.g. invasive and native urban specialists and generalist species). Yet, as populations continue to grow, competition can appear between those groups and it is not yet clear who are the primary 'winners' in the BH process. Here, we analyze trends of common native and non-native birds during the last 15 years across Israel, where large populations of very destructive invasive alien bird species were introduced towards the end of the previous century, using a nation-wide citizen-science program, and two local standardized surveys. Community and population analyses showed that the non-native species are the primary 'winners' of the BH process. Native urban specialists and generalist species that were previously considered as 'winners' are now among the 'losers'. For instance, populations of the invasive common myna increased dramatically, while populations of the previously widespread house sparrow strongly decreased. Previous studies conducted in Israel have shed light on the mechanisms through which invasive bird species can impact native species, notably competition. We show that these processes are among the key factors that drive population declines and changes in bird communities. This highlights the importance of acting now, especially since non-native species are currently spreading from human-dominated areas to more natural environments.